Practicality The Development Of Whole Language Based Bahasa Indonesia Learning - Khurnia Eva Nilasari; Atmazaki; Harris Effendi Thahar; Azwar Ananda (International Conferences on Educational, Social Sciences and Technology)
This reasearch is puposed to explain the practicality of whole language based Bahasa Indonesia learning model. The research is administered through the R & D. The practicality testing is conducted at MTsN Gunung Pangilun (MTsN A) 46 students, MTsN Lubuk Buaya (MTsN B) 28 students, and MTsN Parak Lawas 38 students. The result of the research is received through an observation of learning process, practicality assessment by a practitioner and students. Based on the data, the practicality of research product which is conducted to the schools show the difference of practicality marks. At MTsN A and C is considered practical, meanwhile MTsN C is considered very practical. In fact, the degree of practiclity is also influenced by the number of students in a classroom. The practicality of research product after practicality testing of collaborated model, build a cooperative learning so that it increases communicative interaction correlation and respective manner among students.